THE HUNTING ENCYCLOPEDIA - Conley, Kate; Pearson, Marie (Minneapolis, MN : Encyclopedias, an imprint of Abdo Reference, 2024)
The Hunting Encyclopedia provides readers with in-depth information about hunting. Alongside details about commonly hunted species and hunting gear, readers will learn about hunting strategies, uses for hunted game, the importance of conservation, and how to stay safe while hunting.-- Provided by Publisher.
The hunting tradition -- Game -- Gear -- Firearms, bows, and traps -- Sites, scouting, and tracking -- Hunting strategies -- Hunting with dogs -- After the hunt -- Ethics, conservation, and laws -- Safety.
Includes online resources and index
Keywords: Hunting -- Encyclopedias -- Juvenile literature; Hunting for sport -- Encyclopedias -- Juvenile literature; Recreational hunting -- Encyclopedias -- Juvenile literature; Encyclopedias and dictionaries -- Juvenile literature; Encyclopedias